Types of Presupposition in â€œBBCâ€ Instagram Social Media - Sani Ambarita; Mhd Johan (Institut Agama Islam Negeri Palopo, 2022)
This research describes about usage and type of presupposition found in â€œBBCâ€ twitter. The aim of this research is to find out the types of presupposition and the usage of this presupposition found in the â€œBBC.â€ Type of presupposition can be found in the BBCâ€™s feed. The theory that the researcher used in this study is Yule (2010). The researcher used a qualitative descriptive method. With the data collection method is by observation. The researcher used non participatory to collect the data that means the researcher did not involve to analyze the data. There are 32 data which has relation to the type of presupposition in â€œBBCâ€ Twitter Social Media. Lexical is about 10 data, 6 data contains factive, 5 data is structural, 5 data for non factive, 3 data for existential, 3 data for counter factual. The researcher also found the usage of presupposition. They are Conciseness, Interestingness, Enlargement, Emphasis, Euphemism, Concealment, Persuasion, Self- protection..